Attachment Patterns and Complex Trauma in a Sample of Adults Diagnosed with Gender Dysphoria - Giovanardi, Guido; Vitelli, Roberto; Maggiora Vergano, Carola; Fortunato, Alexandro; Chianura, Luca; Lingiardi, Vittorio; Speranza, Anna Maria (Frontiers in Psychology, 2018)
The current study investigated attachment representations and complex trauma in a sample of gender dysphoric adults. Although it has been proven that the psychological wellbeing of gender diverse persons is largely mediated by family acceptance and support, research on their relationships with parental figures is scarce. A total of 95 adults took part in the study. The attachment distribution was as follows: 27% secure, 27% insecure and 46% disorganised. Regarding early traumas, 56% experienced four or more traumatic forms. Further, gender dysphoric adults showed significantly higher levels of attachment disorganisation and polyvictimisation, relative to controls. Comparisons of subgroups, defined by natal gender, showed that trans women, compared to control males, had more involving and physically and psychologically abusive fathers, and were more often separated from their mothers; trans men, relative to female controls, had more involving mothers and were more frequently separated from and neglected by their fathers. The research has several implications for treatment, clinical health psychology, family support and education.